Identity and architectural values of the monastery of São Bento de Cástris in the period 1957-2005 - Aleixo, Sofia (2017)
Identity is part of the architectural heritage, related directly to the cultural values of the place. In Portugal the monasteries were significantly changed after 1834, reason why they are architectural entities whose materiality reflects the adaptations to which they have been subjected over time, integrating its authenticity. This is the case of the Monastery of São Bento de Cástris, in Évora, which had several uses through time, adapting the place to allow its physical continuity. Through the study of its materiality it was sought to recognize the identity of the place between 1957-2005, when it was used as the male section of Casa Pia, a child care institution. This study aims to contribute to a future intervention methodology that considers the material values of the Monastery, due to the need to safeguard this currently abandoned place. This will contribute to regain a new collective esteem, essential for its continuity.